2014
DOI: 10.1016/j.lfs.2013.12.207
|View full text |Cite
|
Sign up to set email alerts
|

The acute antinociceptive effect of hyperbaric oxygen is not accompanied by an increase in markers of oxidative stress

Abstract: Aims Exposure to hyperbaric oxygen (HBO2) causes an antinociceptive response in mice. However, breathing oxygen (O2) at an elevated pressure can potentially cause oxygen toxicity. The aim of this study was to identify the determinants of HBO2 antinociception and the toxicity profile of HBO2. Main methods Male NIH Swiss mice were assessed for acute antinociceptive responsiveness under room air or 100% O2 at 1.0 or 3.5 atmospheres absolute (ATA), using the acetic acid-induced abdominal constriction test. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In physiological conditions, reactive oxygen species (ROS) are subproducts of oxidative phosphorylation inside the mitochondria (Taniyama and Griendling, ; Liu et al, ; Zhou et al, ; Rönn et al, ). However, in inflammatory conditions, activated macrophages secrete metalloproteinases that increases ROS concentration and the intracellular oxidative stress promoted by this situation can blockade eNOS activity (Vaddi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In physiological conditions, reactive oxygen species (ROS) are subproducts of oxidative phosphorylation inside the mitochondria (Taniyama and Griendling, ; Liu et al, ; Zhou et al, ; Rönn et al, ). However, in inflammatory conditions, activated macrophages secrete metalloproteinases that increases ROS concentration and the intracellular oxidative stress promoted by this situation can blockade eNOS activity (Vaddi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary experiments demonstrated that neither 100% O 2 nor 3.5 ATA alone produced any antinociceptive effect; only the combination of 100% O 2 and 3.5 ATA evoked an antinociceptive response (Liu et al, 2013; Liu et al, unpublished manuscript under review).…”
Section: Methodsmentioning
confidence: 99%
“…HBOT has been shown to promote neuronal survival, decrease the apoptosis of brain injury via a reduction in oxidative stress to modulate neuroinflammation. (Liu et al, 2014 ). Our results showed that HBO intervention could downregulate the expression of histones H1, H2A, H4 induced by TBI, while the decline in 1.6ATA groups was significantly lower than that in the 2.2ATA group, especially within 6 h. It confirmed preliminarily that 1.6ATA HBO might reduce secondary damage of TBI through inhibiting histone release more efficiently than 2.2ATA HBO.…”
Section: Discussionmentioning
confidence: 99%